Who are suitable for low-dose tamsulosin monotherapy as initial treatment strategy in male patients with lower urinary tract symptoms? - Kim, Jae Heon; Shim, Ji Sung; Choi, Hoon; Park, Jae Young; Kwon, Soon Sun; Bae, Jae Hyun (Medicine (United States), 2018)
This study aims to investigate the real indications for low-dose tamsulosin monotherapy for initial treatment. A cross-sectional study was conducted in a total of 1643 patients with lower urinary tract symptoms (LUTS) and with initial lowdose tamsulosin. Initial pretreatment data including the International Prostate Symptoms Score (IPSS), prostate volume, and uroflowmetry data were reviewed. After 8 weeks of treatment, post-treatment IPSS and satisfaction was assessed. Logistic regression analysis was conducted to investigate the pretreatment factors influencing post-treatment satisfaction. Overall satisfaction rate with low-dose tamsulosin as an initial treatment medication was 88.7%. Multivariate analysis revealed that symptom durations, IPSS voiding score, IPSS storage score, and quality of life (QoL) were determinant factors for patient satisfaction. ROC analysis revealed that a urinary score>10 and symptom duration>3 years showed satisfaction with a sensitivity of 85.8% and 90.6%, respectively, and specificity of 43.5% and 39.8%, respectively. Whereas, ROC analysis revealed that a storage score>5 and QoL>3 showed nonsatisfaction with sensitivity of 84.2% and 39.5%, respectively, and specificity of 43.5% and 45.7%, respectively. Multivariate regression analysis demonstrated that voiding score and storage score had a significant relationship with QoL (unstandardized coefficients: 0.073, 0.145, respectively; P-value:<.001,<.001, respectively). The patient with higher storage scores and higher QoL before treatment could have a higher change of non-satisfaction. Combining treatment with anticholinergics could be considered in these patients.
Keywords: Adrenergic alpha-1 Receptor Antagonists; Aged; Cross-Sectional Studies; Humans; Lower Urinary Tract Symptoms; Male; Middle Aged; Patient Satisfaction; Prostatic Hyperplasia; Quality of Life; ROC Curve; Sulfonamides; Treatment Outcome; Urination; Alpha-blocker; Lower urinary tract symptoms; Prostatic hyperplasia; Tamsulosin